Cytotoxic furanosesquiterpenoids and steroids from Ircinia mutans sponges - Fatemeh Heidary Jamebozorgi; Morteza Yousefzadi; Omidreza Firuzi; Melika Nazemi; Somayeh Zare; Jima N. Chandran; Bernd Schneider; Ian T. Baldwin; Amir Reza Jassbi (Taylor & Francis Group, 2021)
Context Ircinia mutans Wilson (Irciniidae) is a sponge with antimicrobial and cytotoxic constituents. Objective Our objective was to characterise the cytotoxic constituents of two seasonal collections of I. mutans. Materials and methods The sponges were extracted in methanol-dichloromethane and their constituents were purified and characterised using column chromatography, GC-MS, 1 D and 2 D NMR. Anti-proliferative activities of the compounds, were evaluated using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) colorimetric assay (0.25-100 μg/mL, 72 h) against leukaemia (MOLT-4), breast (MCF-7) and colon cancer (HT-29) human cells. Results Three furanosesquiterpoids; furodysin (1), ent-furodysinin (2) and furoircin (3) and ten sterols were characterised in I. mutans, for the first time. Cholesterol (4), cholesta-5, 7-dien-3β-ol (5) and ergosterol (6) were determined in the sponge from the winter collections, while cholesta-5, 22-dien-3β-ol (7), 24-methyldesmosterol (8), campesterol (9), stigmasterol (10), γ-ergostenol (11), chondrillasterol (12) and γ-sitosterol (13) were detected in the summer samples. The steroids from the winter collection exhibited cytotoxic activity with IC50 values of 13.0 ± 0.9, 11.1 ± 1.7 and 1.1 ± 0.4 µg/mL, against the mentioned cancer cell lines, respectively, while those from the summer sample, showed greater activity, IC50 = 1.1 ± 0.2 μg/mL against MOLT-4. The purified steroids showed potent MOLT-4 cytotoxic activity, IC50 values = 2.3-7.8 µg/mL. Discussion and conclusion The present study suggests that I. mutans is a rich source of cytotoxic steroids, and introduces 3 as new natural product. Considering the high cytotoxic activity of the steroids, these structures could be candidates for anticancer drug development in future research.